2022
DOI: 10.1021/acs.inorgchem.2c03071
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Thermal Properties of Volatile Group 11 Triazenides as Potential Precursors for Vapor Deposition

Abstract: Group 11 thin films are desirable as interconnects in microelectronics. Although many M−N-bonded Cu precursors have been explored for vapor deposition, there is currently a lack of suitable Ag and Au derivatives. Herein, we present monovalent Cu, Ag, and Au 1,3-di-tert-butyltriazenides that have potential for use in vapor deposition. Their thermal stability and volatility rival that of current state-of-the-art group 11 precursors with bidentate M−N-bonded ligands. Solution-state thermolysis of these triazenide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…21,22,[27][28][29] The group 11 triazenides have great promise as single-source precursors, whilst the group 14 triazenides have desirable thermal and volatility properties. 24,26 During our studies, volatile and thermally stable lanthanide dialkyltriazenides have also been reported. 30 With the success of the triazenide ligand to produce volatile and thermally stable metal compounds, we decided to investigate its reactivity with divalent Zn.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…21,22,[27][28][29] The group 11 triazenides have great promise as single-source precursors, whilst the group 14 triazenides have desirable thermal and volatility properties. 24,26 During our studies, volatile and thermally stable lanthanide dialkyltriazenides have also been reported. 30 With the success of the triazenide ligand to produce volatile and thermally stable metal compounds, we decided to investigate its reactivity with divalent Zn.…”
Section: Introductionmentioning
confidence: 64%
“…Recently, we reported a range of volatile 1,3-dialkyltriazenide compounds for group 11, 13, and 14 metals. [21][22][23][24][25][26] The Ga and In triazenides have been used as ALD precursors to afford excellent quality thin films of GaN, InN, InGaN, and In 2 O 3 . 21,22,[27][28][29] The group 11 triazenides have great promise as single-source precursors, whilst the group 14 triazenides have desirable thermal and volatility properties.…”
Section: Introductionmentioning
confidence: 99%